Lanthanide perovskite type oxide coated high-nickel ternary positive electrode material and preparation method thereof
The high-nickel ternary cathode material is coated with lanthanide perovskite oxide, which solves the problem of unstable material structure, significantly improves its cycle stability and electrochemical performance, and is suitable for the industrial production of lithium-ion power batteries.
Patent Information
- Application Number
- CN202411717922.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The structure of the high-nickel ternary cathode material is unstable during the charging and discharging process, resulting in rapid attenuation of lithium storage capacity and cycling performance, limiting its large-scale application.
The high-nickel ternary positive electrode material is coated with lanthanide perovskite oxide to form a lanthanide perovskite oxide coating layer to improve the structural and interface stability of the material.
The cyclic stability, rate performance, reversible capacity and first Coulomb efficiency of the high-nickel ternary cathode material are significantly improved, ensuring the efficient stability of the material during charging and discharging.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-nickel ternary positive electrode material and a preparation method thereof, and in particular to a lanthanide perovskite-type oxide-coated high-nickel ternary positive electrode material and a preparation method thereof. Background Art
[0002] High-nickel ternary cathode materials are one of the most promising cathode materials for lithium-ion power batteries in the future due to their low cost and high energy density. However, the biggest disadvantage of high-nickel ternary materials is their poor structural stability and interface stability. The surface particles are very prone to the following phenomena: the phase transition process of layered structure-spinel structure-inactive rock salt phase. This prominent interface problem leads to its structural instability, which causes rapid and substantial attenuation of lithium storage capacity and cycle performance, which will seriously restrict the development of its large-scale application. Therefore, improving the structural stability of high-nickel cathode materials through modification methods such as interface modification is crucial to the development of cathode materials with advantages such as low cost, high performance and high capacity.
[0003] CN114864914A discloses a lithium niobate coated modified lithium ion battery high nickel ternary positive electrode material and a preparation method thereof, wherein an organic acid, a niobium source and a lithium source are added to a dispersion containing a high nickel ternary positive electrode material, and after stirring and evaporating the solvent, the dispersion is calcined to obtain a lithium niobate coated high nickel ternary positive electrode material. Although the method has a simple process, low energy consumption, and can realize the macro-quantity preparation of high performance lithium ion battery positive electrode materials, in the actual operation process, the high nickel ternary material is exposed to a liquid phase environment for a long time, which will have a great impact on the structure of the material itself and is difficult to achieve in industrial production.
[0004] CN116177624A discloses a spinel structure coating modified lithium ion battery high nickel ternary positive electrode material and preparation method, which is to prepare a nickel cobalt manganese precursor with a surface rich in manganese elements by coprecipitation reaction, and then fully mix the nickel cobalt manganese precursor with lithium salt, and roast it in an oxygen atmosphere according to a three-stage program temperature control heating method to obtain a high nickel ternary positive electrode material with a spinel structure coating. Although the method has a simple preparation process, a low reaction temperature, and can significantly improve the cyclic stability of the material, in the actual operation process, the control conditions are relatively strict, and the Mn content on the surface of the material is difficult to accurately control, and it is generally difficult to be widely promoted and used in industrial production.
[0005] CN114566647A discloses a method for preparing a calcium phosphate coated high nickel ternary positive electrode material, which comprises adding a calcium source solution to an organic solvent or water, stirring evenly, then adding a high nickel ternary positive electrode material and the phosphorus source solution, heating and drying, and obtaining a powder material; and calcining the powder material to obtain a calcium phosphate coated high nickel ternary positive electrode material. Although sintering after coating the surface of the high nickel ternary positive electrode material with calcium phosphate can effectively reduce the residual lithium on the surface of the high nickel ternary material, reduce the occurrence of side reactions, and improve its storage performance, the structural compatibility between the phosphate coated material and the high nickel ternary material is not ideal, which may lead to an unstable interface or form an uneven coating layer, which will affect the conductivity and ion migration ability of the material.
[0006] CN114853089A discloses a method for preparing a magnesium borate-coated high-nickel ternary positive electrode material, which comprises mixing a lithium source and a ternary precursor evenly, sintering under high temperature conditions in an oxygen atmosphere, and then cooling to room temperature, crushing and sieving to obtain a primary sintering material powder; mixing the sintering material powder and magnesium borate evenly, coating and sintering under high temperature conditions, and cooling to room temperature to obtain a magnesium borate-coated high-nickel ternary positive electrode material. Although this method can significantly reduce the residual alkali content, reduce the powder resistance of the material, and improve the cycle and rate performance of the material, the cost may limit the competitiveness of the magnesium borate-coated high-nickel ternary positive electrode material in low-cost, large-scale applications.
[0007] CN109256557A discloses a perovskite-type oxide-coated high-nickel layered oxide lithium battery positive electrode material and a preparation method thereof, wherein a nickel source, a cobalt source and a manganese source are dissolved to obtain a mixed metal salt solution, an inorganic strong base and an ammonia solution are added to adjust the pH, and a high-nickel ternary precursor material is obtained by stirring, reacting, filtering, washing, and drying; and then mixed and calcined with a lithium source, and then mixed and calcined with a lanthanum source and an aluminum source, and after grinding, a perovskite-type oxide-coated high-nickel modified high-nickel ternary layered positive electrode material is obtained. Although the preparation method of the method is simple in process, the rate performance and cycle performance of the prepared material are relatively excellent, and good cycle stability can still be maintained under high temperature and high pressure test conditions, the perovskite material is directly generated by solid phase reaction and coated, and there are problems such as large product particles, wide particle size distribution range, and poor consistency of the product caused by uneven reaction.
[0008] In summary, it is urgent to find a lanthanide perovskite oxide-coated high-nickel ternary positive electrode material with high lithium ion and electron conductivity, highly reversible charge and discharge reaction, stable thermodynamic structure, high safety, good rate performance and cycle stability during the charge and discharge process, as well as a preparation method for the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material that is simple and controllable, has a short process flow, good coating effect, low cost, and is suitable for industrial production. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a lanthanide perovskite oxide-coated high-nickel ternary positive electrode material with high lithium ion and electron conductivity, highly reversible charge and discharge reaction, stable thermodynamic structure, high safety, good rate performance and cycle stability during the charge and discharge process.
[0010] The technical problem further to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a lanthanide perovskite-type oxide-coated high-nickel ternary positive electrode material that is simple and controllable, has a short process flow, good coating effect, low cost, and is suitable for industrial production.
[0011] The technical solution adopted by the present invention to solve the technical problem is as follows: a lanthanide perovskite oxide coated high-nickel ternary positive electrode material, wherein the lanthanide perovskite oxide coated high-nickel ternary positive electrode material is a spherical particle formed by coating the high-nickel ternary positive electrode material with a lanthanide perovskite oxide coating layer at a mass ratio of 0.01 to 0.03:1; the chemical formula of the lanthanide perovskite oxide is La z Ca 1-z CoO3, wherein 0.5≤z≤1.0; the chemical formula of the high nickel ternary positive electrode material is LiNi x Co y Mn (1-x-y) O2, wherein 0.80≤x≤0.96 (more preferably 0.90≤x≤0.96), 0.01≤y≤0.10 (more preferably 0.01≤y≤0.03), 1-xy>0. z Ca 1-z As a typical oxygen ion conductor, CoO3 has the advantages of low price, high oxygen mobility, good structural stability, etc. It can also stabilize oxygen vacancies / interstices and inhibit the reactivity of surface lattice oxygen ions. After coating the positive electrode material, it can effectively inhibit the release of lattice oxygen, irreversible phase transition and the generation of intercrystalline microcracks, thereby significantly improving the structural and interface stability of the material and effectively improving its electrochemical performance. The present invention creatively proposes a lanthanide perovskite oxide La z Ca 1-z CoO3 coated high nickel ternary cathode material enables it to give full play to the advantages of good structural stability of perovskite oxide and ability to inhibit the reactivity of surface lattice oxygen ions during the cycle. z Ca 1-z After the CoO3 coating, the high nickel ternary positive electrode material not only improves the cycle stability during the charge and discharge cycle, but also ensures the rapid deintercalation reaction of the layered high nickel ternary positive electrode material; z Ca 1-zCoO3 coated materials can improve the interface stability and structural stability of materials, effectively inhibit the erosion of electrolytes, phase changes and the release of lattice oxygen, reduce the dissolution of transition metals in active materials, reduce the occurrence of side reactions and gas generation during electrode polarization and cycling, and thus significantly improve the cycle performance, rate performance, reversible capacity and first coulomb efficiency of high nickel ternary cathode materials, showing excellent electrochemical performance. ABO3 type perovskite oxides have the advantages of low price, good redox performance, high oxygen mobility and good thermal stability. Among them, lanthanum has high thermal stability, which can ensure that perovskite materials still have excellent stability under extreme working conditions. Therefore, La is determined as the A-site element; Ca 2+ and La 3+ The ionic radius of Ca 2+ Substitution at the La position can further enhance the structural stability of perovskite materials, and due to its wide availability, low price, and relatively weak Ca-O bond strength, it is considered to be a promising A-site dopant. Based on the advantages of Co in ternary positive electrode materials, such as being able to stabilize the layered structure of the material and reduce cation mixing, which is beneficial to battery cycling performance, Co was determined to be a B-site element.
[0012] Preferably, the high-nickel ternary positive electrode material is a typical layered structure, and the three elements Ni, Co and Mn are evenly distributed in the high-nickel ternary positive electrode material.
[0013] Preferably, the average particle size of the lanthanide perovskite oxide-coated high-nickel ternary cathode material is 2 to 8 μm. When the secondary particles of the lanthanide perovskite oxide-coated high-nickel ternary cathode material are within the particle size, the rapid diffusion kinetics of lithium ions inside the particles can be ensured, and the agglomeration of the material during storage can be avoided, which deteriorates the electrochemical performance.
[0014] Preferably, the average thickness of the lanthanide perovskite oxide coating layer is 2 to 6 nm. The coating layer should not be too thick or too thin. A too thick coating layer will lead to poor contact between particles and increase interface impedance; while a too thin coating layer may not be able to effectively protect the electrode material, which may easily lead to deterioration of the material structure and electrochemical performance.
[0015] The technical solution adopted by the present invention to further solve its technical problems is as follows: a method for preparing a lanthanide perovskite oxide-coated high-nickel ternary positive electrode material, comprising ball-milling and mixing the lanthanide perovskite oxide and the high-nickel ternary positive electrode material, and sintering them at a low temperature under a protective atmosphere.
[0016] The inventive idea of the method of the present invention is to obtain a lanthanide perovskite oxide La having a conductive network structure by ball milling and low-temperature solid-phase sintering in a protective atmosphere. z Ca 1-zCoO3 coated high nickel ternary cathode material. Since the original material has a very high nickel content, liquid phase coating can easily cause the material to absorb moisture, resulting in an increase in residual alkali on the surface. Therefore, solid phase coating is used to form and enhance the coating layer through the diffusion, chemical reaction, and mutual dissolution of substances at the solid phase interface, thereby improving the stability of the material.
[0017] Preferably, the mass ratio of the lanthanide perovskite oxide to the high-nickel ternary positive electrode material is 0.01 to 0.03:1. Too high a coating amount may increase the diffusion path of electrons and lithium ions, reduce the electrochemical reaction rate and ion transfer rate of the active material, and lead to a decrease in the electrochemical performance of the positive electrode material; on the contrary, too low a coating amount will cause the active material to still be exposed to the electrolyte, which is easy to damage the solid electrolyte interface (SEI) layer and corrode the electrode material, resulting in a decrease in the safety and cycle life of the battery; within the coating amount range, the electrochemical performance of the material can be optimized to the greatest extent.
[0018] Preferably, the ball milling mixing speed is 100-300 r / min (more preferably 150-200 r / min), and the time is 2-10 h (more preferably 4-8 h). Selecting a lower speed can avoid the crushing of secondary particles due to violent collision between ball milling beads and secondary particles, which causes the collapse and disintegration of the layered positive electrode material structure and deterioration of electrochemical performance; in addition, solid phase coating requires controlling the appropriate ball milling time, which should not be too long or too short. Too long ball milling time will cause cracks or damage on the surface of the positive electrode material particles, making it difficult for the coating material to completely cover the particle surface, reducing the coating effect; while too short ball milling time will result in a higher surface roughness of the particles, and the coating material cannot completely cover the particle surface, which will also affect the coating effect.
[0019] Preferably, the protective atmosphere includes argon and / or nitrogen.
[0020] Preferably, the low-temperature sintering is carried out by heating the material to 300-550°C (more preferably 450-550°C) at a rate of 1-10°C / min (more preferably 2-8°C / min) and sintering for 2-10 hours (more preferably 4-8 hours). Low-temperature sintering helps to better combine the coating layer with the base material, thereby improving the mechanical properties and stability of the material. The sintering temperature range does not exceed the thermal stability range of the base material, and therefore will not destroy the structural stability of the base material, and is within a reasonable low-temperature sintering range; in addition, the low-temperature sintering process requires sufficient reaction time, but too long a reaction time will increase energy consumption and cause unnecessary waste of resources.
[0021] Preferably, the method for preparing the lanthanide perovskite-type oxide comprises the following steps: 1) adding a lanthanum source, a calcium source and a cobalt source into a solvent, and dispersing them by ultrasonic method to obtain a metal ion mixed solution; adding a complexing agent into a solvent, and dispersing them by ultrasonic method to obtain a complexing agent solution; 2) adding the complexing agent solution obtained in step 1) drop by drop into the metal ion mixed solution obtained in step 1), or adding the metal ion mixed solution obtained in step 1) drop by drop into the complexing agent solution obtained in step 1), performing a stirring reaction, heating, performing a second stirring reaction, drying, ball milling, sintering in an oxidizing atmosphere, and cooling to room temperature to obtain a lanthanide perovskite oxide.
[0022] Preferably, in step 1), the molar ratio of lanthanum in the lanthanum source, calcium in the calcium source and cobalt in the cobalt source is 0.5-1.0:0-0.5:1. Lanthanum is a determined A-position element, and to ensure that the coating material has strong stability, its A-position ratio must be ≥50%, calcium is an A-position doping element, which plays a role in assisting in stabilizing the material structure, and its A-position ratio must be ≤50%, and cobalt is a determined B-position element, and B-position doping is not considered, and its B-position ratio is 100%.
[0023] Preferably, in step 1), the total molar concentration of metal ions in the metal ion mixed solution is 0.1-0.9 mol / L (more preferably 0.2-0.7 mol / L). The molar concentration of metal ions will affect the crystal structure of the product. A lower concentration may lead to the formation of amorphous or small-particle crystals, while a higher concentration may lead to the formation of larger crystals or multiple phases. Within the concentration range, the solvation, hydrolysis reaction and polycondensation reaction can proceed normally, and the product crystal form is complete and the particle size distribution is uniform.
[0024] Preferably, in step 1), the lanthanum source includes one or more of lanthanum nitrate, lanthanum acetate or lanthanum chloride, and hydrates thereof.
[0025] Preferably, in step 1), the calcium source includes one or more of calcium nitrate, calcium acetate or calcium chloride, and hydrates thereof.
[0026] Preferably, in step 1), the cobalt source includes one or more of cobalt nitrate, cobalt acetate or cobalt chloride, and hydrates thereof.
[0027] Preferably, in step 1), the concentration of the complexing agent solution is 0.1 to 0.8 mol / L (more preferably 0.12 to 0.50 mol / L). A complexing agent solution of appropriate concentration can effectively stabilize metal ions and prevent them from aggregation or precipitation. A lower complexing agent concentration may not be able to fully complex metal ions, and the concentration of the complexing agent will also affect the rate of the gelation process. An ideal complexing agent concentration can promote cross-linking between molecules and enable rapid gel formation. The concentration range can ensure the normal progress of the gelation reaction, which is conducive to the synthesis of a gel product with uniform morphology and particle size distribution.
[0028] Preferably, in step 1), the complexing agent includes one or more of citric acid, ethylenediaminetetraacetic acid or ethylene glycol.
[0029] Preferably, in step 1), the solvent is a mixed solvent of anhydrous ethanol and deionized water in a volume ratio of 1:1 to 3. As polar solvents, water and ethanol can effectively dissolve metal salts to form a uniform sol; ethanol helps to regulate the reaction rate and promote polymerization reaction to form a more stable polymer network, while water has strong hydrophilicity and helps to form a more uniform sol. Therefore, the mixed use of the two is conducive to improving the output efficiency of the sol-gel method and the performance of the final material.
[0030] Preferably, in step 1), the frequency of the ultrasonic dispersion is 30 to 60 kHz, and the time is 1 to 4 h.
[0031] Preferably, in step 2), the volume ratio of the complexing agent solution to the metal ion mixed solution is 1:0.4-4.0 (more preferably 1:0.6-2.6). When the lanthanum source, calcium source and cobalt source are solutes that are easily precipitated, such as acetate, the metal ion mixed solution is added dropwise to the complexing agent solution to avoid the formation of precipitated impurities.
[0032] Preferably, in step 2), the molar ratio of the complexing agent in the complexing agent solution to the cobalt ions in the metal ion mixed solution is 1.0 to 1.5:1.
[0033] The appropriate volume ratio of the complexing agent solution and the metal ion mixed solution, as well as the molar ratio of the complexing agent to the cobalt ions can improve the crystallinity of the material, make the particles more uniform and the morphology more complete. If the ratio is too large or too small, it may lead to a decrease in the crystallinity of the material, uneven particle size, and even the formation of disordered particle aggregates.
[0034] Preferably, in step 2), the dripping rate is 60 to 120 mL / h. The dripping rate of the complexing agent will affect the reaction process. If the dripping rate is too fast, the reaction may be accelerated, resulting in rapid aggregation of metal ions and uneven phase separation or precipitation. Therefore, the complexing agent needs to be dripped slowly so that the reaction is carried out over a longer period of time to ensure uniform dispersion of metal ions and maintain good uniformity in the entire reaction system to obtain a more uniform and stable gel structure.
[0035] Preferably, in step 2), during the dropping process, the metal ion mixed solution or complexing agent solution to be dropped is stirred at a stirring speed of 100 to 600 r / min.
[0036] Preferably, in step 2), the temperature of the first stirring reaction is 20-30°C, the stirring speed is 100-600r / min, and the time is 10-20 hours. The first stirring reaction is preferably temperature-controlled in a water bath. Using lanthanum source, calcium source, and cobalt source as raw materials, in a solvent containing a complexing agent, a single stirring reaction can ensure uniform complexation without precipitation.
[0037] Preferably, in step 2), the temperature is raised to 30-80°C.
[0038] Preferably, in step 2), the temperature of the secondary stirring reaction is 30-80°C, the stirring speed is 100-600r / min, and the time is 8-14 hours. During the secondary stirring process, the complex product undergoes a sol-gel reaction to synthesize a precursor of a lanthanide perovskite oxide with a complete crystal structure. Since the sol-gel method can ensure strict control of the stoichiometric ratio, the obtained product has high purity, small particle size, and uniform distribution. The gel contains a large amount of liquid phase or pores, and it is not easy to agglomerate the particles during the heat treatment process, avoiding the problems of non-uniform particle size, incomplete reaction, and particle agglomeration of the synthesized material in pure solid-phase reaction.
[0039] Preferably, in step 2), the drying is vacuum drying.
[0040] Preferably, the vacuum drying temperature is 80 to 120° C., the vacuum degree is -0.06 to -0.09 MPa, and the time is 6 to 12 h.
[0041] Preferably, in step 2), the ball milling speed is 300-700 r / min, and the time is 2-10 h.
[0042] Preferably, in step 2), the oxidizing atmosphere includes oxygen atmosphere and / or air atmosphere.
[0043] Preferably, in step 2), the sintering is a two-stage temperature-raising sintering, firstly heating to 350-550°C (more preferably 400-500°C) at a rate of 1-10°C / min (more preferably 3-6°C / min), sintering for 2-10 h (more preferably 2-6 h), and then heating to 600-900°C (more preferably 700-800°C) at a rate of 1-10°C / min (more preferably 3-6°C / min), sintering for 9-16 h (more preferably 12-15 h). High-temperature sintering can promote the formation of perovskite phase, which is very important for preparing materials with stable crystal structure. In addition, high-temperature sintering can remove excess solvents, gases and other volatile substances generated during the synthesis process, thereby improving the density and mechanical strength of the final material. The calcination time, calcination temperature and heating rate range can promote crystallization, increase density, improve microstructure and optimize the comprehensive properties of the material to the greatest extent.
[0044] Preferably, the preparation method of the high-nickel ternary positive electrode material is: grind and mix the nickel cobalt manganese hydroxide precursor and the lithium source, sinter them in an oxidizing atmosphere, and cool them to room temperature.
[0045] Preferably, the chemical formula of the nickel cobalt manganese hydroxide precursor is Ni x Co y Mn (1-x-y) (OH)2, wherein 0.80≤x≤0.96, 0.01≤y≤0.10, 1-xy>0.
[0046] Preferably, the average particle size of the nickel cobalt manganese hydroxide precursor is 2 to 8 μm.
[0047] Preferably, the molar ratio of the total molar number of Ni, Co, and Mn in the nickel cobalt manganese hydroxide precursor to the molar ratio of Li in the lithium source is 1:1.01 to 1.08.
[0048] Preferably, the lithium source comprises LiOH·H2O and / or Li2CO3.
[0049] Preferably, the grinding speed is 100 to 300 r / min and the grinding time is 12 to 48 min.
[0050] Preferably, the oxidizing atmosphere includes an oxygen atmosphere and / or an air atmosphere, etc.
[0051] Preferably, the sintering is a two-stage temperature-raising sintering, firstly heating to 350-550 °C (more preferably 400-500 °C) at a rate of 1-10 °C / min (more preferably 3-7 °C / min), sintering for 2-6 h (more preferably 3-5 h), and then heating to 550-800 °C (more preferably 600-700 °C) at a rate of 1-10 °C / min (more preferably 3-7 °C / min), sintering for 8-14 h (more preferably 10-13 h). During the two-stage temperature-raising sintering process, the temperature of the second sintering stage is higher than the temperature of the first sintering stage. During the first stage of sintering, the decomposition reaction of the high-nickel ternary precursor and the lithium source mainly occurs, and during the second stage of sintering, the chemical reaction of the high-nickel ternary precursor and the oxide decomposed by the lithium source in an oxygen atmosphere mainly occurs. If the sintering temperature is too high or the time is too long, the material is prone to agglomeration or even agglomeration, and it is difficult to release capacity during the charge and discharge process. If the calcination temperature is too low or the time is too short, it is difficult to form the desired morphology, affecting the electrochemical performance. If the heating rate is too fast, it is difficult to ensure sufficient material reaction, especially affecting the diffusion of lithium ions into the material structure. If the heating rate is too slow, it is not conducive to industrial production.
[0052] The protective atmosphere or oxygen atmosphere used in the present invention is a high-purity gas with a purity of ≥99.99%.
[0053] The beneficial effects of the present invention are as follows: (1) The lanthanide perovskite oxide coated high nickel ternary cathode material of the present invention is uniformly coated, and the secondary particles are spherical in shape with an average particle size of 2 to 8 μm, which inherits the spherical morphology of the high nickel ternary precursor. The surface of the secondary particles is relatively rough, and many tiny particles are attached, that is, a lanthanide perovskite oxide coating layer with a uniform average thickness of 2 to 6 nm is formed, and the three elements Ni, Co, and Mn are uniformly distributed in the high nickel ternary cathode material; (2) The battery assembled with the lanthanide perovskite oxide coated high nickel ternary positive electrode material of the present invention has a first discharge specific capacity of 222.9 mAh / g, 201.6 mAh / g, and 192.2 mAh / g at current densities of 0.2 C (40 mAh / g), 5 C, and 10 C, respectively, indicating that the positive electrode material can maintain good structural stability during the charge and discharge process, the charge and discharge reaction is highly reversible, and the rate performance is good; at a charge and discharge voltage of 2.7 to 4.3 V and a current density of 1 C, the first discharge specific capacity can be as high as 221.4 mAh / g. After 100 cycles, the discharge specific capacity can be as high as 198.17 mAh / g, and the retention rate can be as high as 92.61%, indicating that the lanthanide perovskite oxide coated high nickel ternary positive electrode material of the present invention has a stable thermodynamic structure, high safety, and good cycle stability; (3) The method of the present invention is simple and controllable, has a short process flow, good coating effect, low cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The lanthanide perovskite oxide La obtained in Reference Example 1 of the present invention 0.8 Ca 0.2 XRD pattern of CoO3; Figure 2 The lanthanide perovskite oxide La obtained in Reference Example 1 of the present invention 0.8 Ca 0.2 SEM image of CoO3; Figure 3 The lanthanide perovskite oxide La of Example 1 of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 XRD pattern of O2 cathode material; Figure 4 Example 1 of the present invention: lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co0.03 Mn 0.01 SEM image of O2 cathode material; Figure 5 Example 1 of the present invention: lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 TEM image of O2 cathode material; Figure 6 Example 1 of the present invention: lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Rate curve of the battery assembled with O2 positive electrode material; Figure 7 Example 1 of the present invention: lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Discharge cycle curve of the battery assembled with O2 positive electrode material; Figure 8 Example 2 of the present invention: lanthanide perovskite oxide La 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Discharge cycle curve of the battery assembled with O2 positive electrode material; Fig. 9 Example 3 of the present invention: lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Discharge cycle curve of the battery assembled with O2 positive electrode material; Fig.10 The high nickel ternary LiNi 0.96 Co 0.03 Mn 0.01 Discharge cycle curve of the battery assembled with O2 positive electrode material; Fig.11 The synthetic lanthanide perovskite oxide La used in Comparative Example 2 of the present invention 0.8 Ca 0.2 XRD pattern of CoO3; Fig.12The synthetic lanthanide perovskite oxide La used in Comparative Example 2 of the present invention 0.8 Ca 0.2 SEM image of CoO3; Fig.13 The lanthanide perovskite oxide La is a comparative example 2 of the present invention. 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Discharge cycle curve of the battery assembled with O2 positive electrode material; Fig.14 The lanthanide perovskite oxide La is a comparative example 3 of the present invention. 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Discharge cycle curve of the battery assembled with O2 positive electrode material. DETAILED DESCRIPTION
[0055] The present invention will be further described below in conjunction with the embodiments and drawings.
[0056] The lanthanum nitrate, cobalt nitrate and calcium nitrate used in the examples and comparative examples of the present invention were all purchased from Aladdin Reagent Co., Ltd.; the purity of the high-purity gas used was 99.99%; the raw materials or chemical reagents used in the examples and comparative examples of the present invention were obtained through conventional commercial channels unless otherwise specified.
[0057] Lanthanide perovskite oxide La 0.8 Ca 0.2 Preparation method of CoO3 Reference Example 1 1) Add 1.5588 g (0.0036 mol) of lanthanum nitrate hexahydrate, 0.2125 g (0.0009 mol) of calcium nitrate tetrahydrate and 1.3096 g (0.0045 mol) of cobalt nitrate hexahydrate into 30 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1), and disperse them ultrasonically at an ultrasonic frequency of 50 kHz for 2 h to obtain a metal ion mixed solution; add 0.9456 g (0.0045 mol) of citric acid monohydrate into 20 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1), and disperse them ultrasonically at an ultrasonic frequency of 50 kHz for 2 h to obtain a 0.225 mol / L citric acid solution; 2) 20 mL of 0.225 mol / L citric acid solution obtained in step 1) was added dropwise at a rate of 90 mL / h into 30 mL of the metal ion mixed solution obtained in step 1) which was stirred at a stirring speed of 300 r / min. The mixture was stirred for 12 h at a water bath temperature of 25 °C and a stirring speed of 300 r / min. After the mixture was heated to 50 °C, the mixture was stirred for 10 h at 50 °C and a stirring speed of 300 r / min. After the gel was formed, the mixture was vacuum dried at 100 °C and -0.07 MPa for 10 h. After the mixture was ball milled at a speed of 600 r / min for 6 h, the mixture was sintered in two stages in a high-purity oxygen atmosphere. The mixture was first heated to 480 °C at a rate of 5 °C / min, sintered for 6 h, and then heated to 750 °C at a rate of 5 °C / min, sintered for 12 h, and cooled to room temperature to obtain lanthanide perovskite oxide La. 0.8 Ca 0.2 CoO3.
[0058] like Figure 1 As shown, the lanthanide perovskite oxide La obtained in Reference Example 1 of the present invention 0.8 Ca 0.2 CoO3 and La 0.8 Ca 0.2 The characteristic peaks on the standard PDF card (PDF#36-1388) of CoO3 are consistent, and the crystal structure is complete.
[0059] like Figure 2 As shown, the lanthanide perovskite oxide La obtained in Reference Example 1 of the present invention 0.8 Ca 0.2 CoO3 is a porous mesh material with good conductivity, which is conducive to the transmission of lithium ions.
[0060] Lanthanide perovskite oxide La 0.5 Ca 0.5 Preparation method of CoO3 Reference Example 2 1) Add 1.0825 g (0.0025 mol) of lanthanum nitrate hexahydrate, 0.5904 g (0.0025 mol) of calcium nitrate tetrahydrate and 1.4552 g (0.0050 mol) of cobalt nitrate hexahydrate into 30 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1), and disperse them ultrasonically at an ultrasonic frequency of 40 kHz for 1 h to obtain a metal ion mixed solution; add 1.0717 g (0.0051 mol) of citric acid monohydrate into 20 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1), and disperse them ultrasonically at an ultrasonic frequency of 40 kHz for 1 h to obtain a 0.255 mol / L citric acid solution; 2) 20 mL of 0.255 mol / L citric acid solution obtained in step 1) was added dropwise at a rate of 100 mL / h to 30 mL of the metal ion mixed solution obtained in step 1) stirred at a stirring speed of 450 r / min, and a stirring reaction was carried out at a water bath temperature of 25 ° C and a stirring speed of 450 r / min for 14 h. After heating to 60 ° C, a second stirring reaction was carried out at 60 ° C and a stirring speed of 300 r / min for 9 h. After forming a gel, it was vacuum dried at 90 ° C and -0.08 MPa for 12 h, ball milled at a speed of 650 r / min for 6 h, and then sintered in a high-purity oxygen atmosphere in two stages, first heated to 480 ° C at a rate of 5 ° C / min, sintered for 6 h, and then heated to 750 ° C at a rate of 5 ° C / min, sintered for 12 h, and cooled to room temperature to obtain lanthanide perovskite oxide La 0.5 Ca 0.5 CoO3.
[0061] After testing, the lanthanide perovskite oxide La obtained in Reference Example 2 of the present invention 0.5 Ca 0.5 CoO3 and La 0.8 Ca 0.2 The characteristic peaks on the standard PDF card (PDF#36-1388) of CoO3 are consistent, and the crystal structure is complete.
[0062] After testing, the lanthanide perovskite oxide La obtained in Reference Example 2 of the present invention 0.5 Ca 0.5 CoO3 is a porous mesh material with good conductivity, which is conducive to the transmission of lithium ions.
[0063] Lanthanide perovskite oxide La 0.8 Ca 0.2 Preparation method of CoO3 Reference example 3 1) 1.2350 g (0.0036 mol) of lanthanum acetate sesquihydrate, 0.1586 g (0.0009 mol) of calcium acetate monohydrate and 1.1209 g (0.0045 mol) of cobalt acetate tetrahydrate were added to 20 mL of solvent (the volume ratio of anhydrous ethanol to deionized water was 1:2), and ultrasonically dispersed for 3 h at an ultrasonic frequency of 60 kHz to obtain a metal ion mixed solution; 0.9456 g (0.0045 mol) of citric acid monohydrate was added to 30 mL of solvent (the volume ratio of anhydrous ethanol to deionized water was 1:2), and ultrasonically dispersed for 3 h at an ultrasonic frequency of 60 kHz to obtain a 0.15 mol / L citric acid solution; 2) 20 mL of the metal ion mixed solution obtained in step 1) was added dropwise at a rate of 80 mL / h to 30 mL of 0.15 mol / L citric acid solution obtained in step 1) stirred at a stirring speed of 450 r / min, and a stirring reaction was carried out at a water bath temperature of 25 ° C and a stirring speed of 500 r / min for 14 h. After heating to 60 ° C, a second stirring reaction was carried out at 60 ° C and a stirring speed of 500 r / min for 11 h. After forming a gel, it was vacuum dried at 100 ° C and -0.09 MPa for 12 h, ball milled at a speed of 700 r / min for 8 h, and then sintered in a high-purity oxygen atmosphere in two stages, firstly heated to 500 ° C at a rate of 6 ° C / min, sintered for 5 h, and then heated to 720 ° C at a rate of 6 ° C / min, sintered for 14 h, and cooled to room temperature to obtain lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3.
[0064] After testing, the lanthanide perovskite oxide La obtained in Reference Example 3 of the present invention 0.8 Ca 0.2 CoO3 and La 0.8 Ca 0.2 The characteristic peaks on the standard PDF card (PDF#36-1388) of CoO3 are consistent, and the crystal structure is complete.
[0065] After testing, the lanthanide perovskite oxide La obtained in Reference Example 3 of the present invention 0.8 Ca 0.2 CoO3 is a porous mesh material with good conductivity, which is conducive to the transmission of lithium ions.
[0066] Reference Example 4 for the preparation of lanthanide perovskite oxide LaCoO3 The difference between this reference example and reference example 1 is that: in step 1), 1.9485 g (0.0045 mol) of lanthanum nitrate hexahydrate and 1.3097 g (0.0045 mol) of cobalt nitrate hexahydrate are added to 30 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1); in step 2), lanthanide perovskite oxide LaCoO3 is obtained. The rest is the same as reference example 1.
[0067] After testing, the lanthanide perovskite oxide LaCoO3 obtained in Reference Example 4 of the present invention has characteristic peaks consistent with those on the standard PDF card (PDF# 25-1060) of LaCoO3, and has a complete crystal structure.
[0068] After testing, the lanthanide perovskite oxide LaCoO3 obtained in Reference Example 4 of the present invention is a porous network material with good conductivity, which is conducive to the transmission of lithium ions.
[0069] High Nickel LiNi 0.96 Co 0.03 Mn 0.01 Preparation method of O2 positive electrode material Reference example 5 10.0 g of Ni with an average particle size of 4 μm was added 0.96 Co 0.03 Mn 0.01 The (OH)2 precursor (Ni 0.1036 mol, Co 0.00324 mol, Mn 0.00108 mol) and 4.65 g (0.1108 mol) of lithium hydroxide monohydrate were added to an agate mortar and ground at a speed of 150 r / min for 30 min until mixed. Then, a two-stage temperature-raising sintering was carried out in a high-purity oxygen atmosphere. The temperature was first raised to 450 ℃ at a rate of 5 ℃ / min, sintered for 4 h, and then raised to 675 ℃ at a rate of 5 ℃ / min, sintered for 12 h, and cooled to room temperature to obtain high-nickel LiNi with an average particle size of 4 μm. 0.96 Co 0.03 Mn 0.01 O2 cathode material; The Ni 0.96 Co 0.03 Mn 0.01 The (OH)2 precursor was prepared by the hydroxide coprecipitation method, and the specific operation was as follows: 1) Add 2018.66 g (7.68 mol) of nickel sulfate hexahydrate, 67.48 g (0.24 mol) of cobalt sulfate heptahydrate, and 13.52 g (0.08 mol) of manganese sulfate monohydrate into 2 L of deionized water to prepare a metal ion mixed solution with a metal concentration of 4 mol / L; 2) Add 399.96 g (10 mol) of NaOH to 2 L of deionized water to prepare a NaOH solution with a concentration of 5 mol / L; 3) 2 L of the metal ion mixed solution obtained in step 1) was pumped into a reactor containing 2 L of 2 mol / L ammonia solution and purged with argon at a flow rate of 100 mL / h, and at the same time, the ammonia concentration of the reaction system was adjusted to 2 mol / L with 25% ammonia solution, and the NaOH solution obtained in step 2) was passed into the reactor to adjust the pH value of the reaction system to 11.45; 4) Heat and stir at 40°C and 800 r / min to carry out coprecipitation reaction until the particle size distribution is uniform and the average particle size is 4 μm, then stop stirring, age for 12 h, wash, filter and dry the filter cake to obtain Ni 0.96 Co 0.03 Mn 0.01 (OH)2 precursor material.
[0070] Lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 O2 positive electrode material embodiment 1 The lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material is the lanthanide perovskite oxide La obtained in Reference Example 1. 0.8 Ca 0.2 The CoO3 coating layer is coated with the high nickel LiNi obtained in Reference Example 5 at a mass ratio of 0.015:1 0.96 Co 0.03 Mn 0.01 Spherical particles formed by O2 positive electrode material; the LiNi 0.96 Co 0.03 Mn 0.01 O2 is a typical layered structure, and the three elements Ni, Co, and Mn are evenly distributed in the high-nickel ternary positive electrode material; the lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The average particle size of the O2 positive electrode material is 4 μm; the lanthanide perovskite oxide La 0.8 Ca 0.2 The average thickness of the CoO3 coating is 3 nm.
[0071] like Figure 3 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The characteristic peaks of the O2 cathode material and the standard PDF card of LiNiO2 (PDF#74-0919) are consistent, indicating that LiNi 0.96 Co 0.03 Mn 0.01 After O2 is coated, its structure is not destroyed and still shows a typical layered structure.
[0072] like Figure 4 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01The morphology of O2 cathode material is better inherited from Ni 0.96 Co 0.03 Mn 0.01 The morphology of the (OH)2 precursor is that the secondary particles are spherical in structure with an average particle size of 4 μm. A layer of lanthanide perovskite-type La is formed on the surface of the secondary particles. 0.8 Ca 0.2 CoO3 coating layer.
[0073] like Figure 5 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The surface of the O2 cathode material is coated with a layer of La 0.8 Ca 0.2 CoO3 perovskite phase material, with an average thickness of 3 nm, and a crystal plane spacing d of 0.228 nm in region I, corresponding to La 0.8 Ca 0.2 The interplanar spacing d of region II of CoO3 (202) plane is 0.205 nm, corresponding to the layered ternary LiNi 0.96 Co 0.03 Mn 0.01 (104) crystal plane of O2 positive electrode material.
[0074] Lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Preparation method of O2 positive electrode material Example 1 0.03 g of the lanthanide perovskite oxide La obtained in Reference Example 1 was added 0.8 Ca 0.2 CoO3 and 2.0 g of high nickel LiNi obtained in Reference Example 5 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material was ball-milled and mixed at a rotation speed of 180 r / min for 6 h, heated to 500 °C at a rate of 5 °C / min in an argon atmosphere, and sintered at low temperature for 6 h.
[0075] In order to test the lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Electrochemical properties of O2 positive electrode materials, and battery assembly: Weigh 0.08 g of lanthanide perovskite La0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 O2 positive electrode material, 0.01 g acetylene black as a conductive agent and 0.01 g PVDF polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are added to mix and grind to form a slurry; the obtained slurry is applied to the surface of aluminum foil to make an electrode piece; in a closed glove box filled with argon, the electrode piece is used as the positive electrode, the metal lithium sheet is used as the negative electrode, the microporous polypropylene membrane is used as the separator, and 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1) is used as the electrolyte to assemble a CR2025 button battery, and the charge and discharge performance test is carried out.
[0076] like Figure 6 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has a discharge specific capacity of 222.9 mAh / g, 201.6 mAh / g and 192.2 mAh / g at current densities of 0.2 C (40 mAh / g), 5 C and 10 C, respectively. This shows that the perovskite material with strong structural stability is coated on the surface of the high-nickel positive electrode material, which effectively stabilizes the structure of the material and can exert a higher capacity even under high rate conditions; when the current density gradually decreases from 10C rate and cycles back to 0.2C rate, the discharge specific capacity can still be as high as 217.5 mAh / g, indicating that the reaction of the positive electrode material is highly reversible during the charge and discharge process.
[0077] like Figure 7 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has an initial discharge capacity of up to 223.1 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7 to 4.3 V. At a current density of 1 C (200 mA / g, starting from the 4th cycle), the initial discharge capacity is 219.3 mAh / g. After 100 cycles, the discharge capacity can still reach 198.17 mAh / g, and the capacity retention rate can reach 90.36%, indicating that the lanthanide perovskite La in the embodiment of the present invention can maintain a good discharge capacity. 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03Mn 0.01 The O2 positive electrode material has good cycle stability.
[0078] Lanthanide perovskite type La 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 O2 positive electrode material embodiment 2 The lanthanide perovskite type La 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The positive electrode material of O2 is the lanthanide perovskite oxide La obtained in Reference Example 2. 0.5 Ca 0.5 The CoO3 coating layer is coated with the high nickel LiNi obtained in Reference Example 5 at a mass ratio of 0.02:1 0.96 Co 0.03 Mn 0.01 Spherical particles formed by O2 positive electrode material; the LiNi 0.96 Co 0.03 Mn 0.01 O2 is a typical layered structure, and the three elements Ni, Co, and Mn are evenly distributed in the high-nickel ternary positive electrode material; the lanthanide perovskite type La 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The average particle size of the O2 positive electrode material is 4 μm; the lanthanide perovskite oxide La 0.5 Ca 0.5 The average thickness of the CoO3 coating is 4 nm.
[0079] After testing, the lanthanide perovskite type La in the embodiment of the present invention 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The characteristic peaks of the O2 cathode material and the standard PDF card of LiNiO2 (PDF#74-0919) are consistent, indicating that LiNi 0.96 Co 0.03 Mn 0.01 After O2 is coated, its structure is not destroyed and still shows a typical layered structure.
[0080] After testing, the lanthanide perovskite type La in the embodiment of the present invention 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co0.03 Mn 0.01 The morphology of O2 cathode material is better inherited from Ni 0.96 Co 0.03 Mn 0.01 The morphology of the (OH)2 precursor is that the secondary particles are spherical in structure with an average particle size of 4 μm. A 4 nm layer of lanthanide perovskite La is formed on the surface of the secondary particles. 0.5 Ca 0.5 CoO3 coating layer.
[0081] Lanthanide perovskite type La 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Preparation method of O2 positive electrode material Example 2 0.04 g of the lanthanide perovskite oxide La obtained in Reference Example 2 was added 0.5 Ca 0.5 CoO3 and 2.0 g of high nickel LiNi obtained in Reference Example 5 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material was ball-milled and mixed at a rotation speed of 170 r / min for 8 h, heated to 550 °C at a rate of 6 °C / min in an argon atmosphere, and sintered at low temperature for 7 h.
[0082] Battery assembly: Same as Example 1.
[0083] like Figure 8 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has an initial discharge capacity of up to 232.7 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7 to 4.3 V. At a current density of 1 C (200 mA / g, starting from the 4th cycle), the initial discharge capacity is 221.4 mAh / g. After 100 cycles, the discharge capacity can still reach 179.1 mAh / g, and the capacity retention rate can reach 80.89%, indicating that the lanthanide perovskite La in the embodiment of the present invention can maintain a good discharge capacity. 0.5 Ca 0.5 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material has good cycle stability.
[0084] Lanthanide perovskite type La0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 O2 positive electrode material embodiment 3 The lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material is the lanthanide perovskite oxide La obtained in Reference Example 3. 0.8 Ca 0.2 The CoO3 coating layer is coated with the high nickel LiNi obtained in Reference Example 5 at a mass ratio of 0.015:1 0.96 Co 0.03 Mn 0.01 Spherical particles formed by O2 positive electrode material; the LiNi 0.96 Co 0.03 Mn 0.01 O2 is a typical layered structure, and the three elements Ni, Co, and Mn are evenly distributed in the high-nickel ternary positive electrode material; the lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The average particle size of the O2 positive electrode material is 4 μm; the lanthanide perovskite oxide La 0.8 Ca 0.2 The average thickness of the CoO3 coating is 3 nm.
[0085] After testing, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The characteristic peaks of the O2 cathode material and the standard PDF card of LiNiO2 (PDF#74-0919) are consistent, indicating that LiNi 0.96 Co 0.03 Mn 0.01 After O2 is coated, its structure is not destroyed and still shows a typical layered structure.
[0086] After testing, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The morphology of O2 cathode material is better inherited from Ni 0.96 Co 0.03Mn 0.01 The morphology of the (OH)2 precursor is that the secondary particles are spherical in structure with an average particle size of 4 μm. A 3 nm layer of lanthanide perovskite La is formed on the surface of the secondary particles. 0.8 Ca 0.2 CoO3 coating layer.
[0087] Lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Example 3 of Preparation Method of O2 Positive Electrode Material 0.045 g of the lanthanide perovskite oxide La obtained in Reference Example 3 was added 0.8 Ca 0.2 CoO3 and 3.0 g of high nickel LiNi obtained in Reference Example 5 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material was ball-milled and mixed for 7 h at a rotation speed of 160 r / min, heated to 450 °C at a rate of 5 °C / min in an argon atmosphere, and sintered at low temperature for 6 h.
[0088] Battery assembly: Same as Example 1.
[0089] like Fig. 9 As shown, the lanthanide perovskite type La in the embodiment of the present invention 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has an initial discharge capacity of up to 213.76 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7 to 4.3 V. At a current density of 1 C (200 mA / g, starting from the 4th cycle), the initial discharge capacity is 213.54 mAh / g. After 100 cycles, the discharge capacity can still reach 197.77 mAh / g, and the capacity retention rate can reach 92.61%, indicating that the lanthanide perovskite La in the embodiment of the present invention can maintain a good discharge capacity. 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material has good cycle stability.
[0090] Lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 O2 positive electrode material embodiment 4 The lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material is a lanthanide perovskite oxide LaCoO3 coating layer obtained in Reference Example 4 coated with the high nickel LiNi obtained in Reference Example 5 at a mass ratio of 0.015:1 0.96 Co 0.03 Mn 0.01 Spherical particles formed by O2 positive electrode material; the LiNi 0.96 Co 0.03 Mn 0.01 O2 is a typical layered structure, and the three elements Ni, Co, and Mn are evenly distributed in the high-nickel ternary positive electrode material; the lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The average particle size of the O2 positive electrode material is 4 μm; the average thickness of the lanthanide perovskite oxide LaCoO3 coating layer is 3 nm.
[0091] After testing, the lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The characteristic peaks of the O2 cathode material and the standard PDF card of LiNiO2 (PDF#74-0919) are consistent, indicating that LiNi 0.96 Co 0.03 Mn 0.01 After O2 is coated, its structure is not destroyed and still shows a typical layered structure.
[0092] After testing, the lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The morphology of O2 cathode material is better inherited from Ni 0.96 Co 0.03 Mn 0.01 The morphology of the (OH)2 precursor is that the secondary particles are spherical in structure with an average particle size of 4 μm, and a 3 nm lanthanide perovskite LaCoO3 coating layer is formed on the surface of the secondary particles.
[0093] Lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 Example 4 of Preparation Method of O2 Positive Electrode Material 0.03 g of the lanthanide perovskite oxide LaCoO3 obtained in Reference Example 4 and 2.0 g of the high-nickel LiNi 0.96 Co 0.03Mn 0.01 The O2 positive electrode material was ball-milled and mixed at a rotation speed of 180 r / min for 6 h, heated to 500 °C at a rate of 5 °C / min in an argon atmosphere, and sintered at low temperature for 6 h.
[0094] Battery assembly: Same as Example 1.
[0095] After testing, the lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has a first discharge capacity of up to 225.03 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7 to 4.3 V, and a first discharge capacity of 218.42 mAh / g at a current density of 1 C (200 mA / g, starting from the 4th cycle). After 100 cycles, the discharge capacity can still reach 175.41 mAh / g, and the capacity retention rate can reach 80.30%, indicating that the lanthanide perovskite LaCoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The O2 positive electrode material has good cycle stability.
[0096] Comparative Example 1 This comparative example is the high nickel LiNi obtained in Reference Example 5 0.96 Co 0.03 Mn 0.01 O2 positive electrode material.
[0097] Battery assembly: Same as Example 1.
[0098] like Fig.10 As shown, the high nickel ternary LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has an initial discharge capacity of 237.67 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7-4.3 V. At a current density of 1C (200 mA / g, starting from the 4th cycle), the initial discharge capacity is 221.30 mAh / g. After 100 cycles, the discharge capacity is only 126.25 mAh / g, and the capacity retention rate is only 57.05%, indicating that the high nickel LiNi 0.96 Co 0.03 Mn 0.01 The cycling stability of O2 positive electrode materials is poor before being coated with lanthanide perovskite oxides.
[0099] Comparative Example 2 The difference between this comparative example and method example 1 is that the lanthanide perovskite oxide La 0.8 Ca 0.2 The only difference between the preparation method of CoO3 and reference example 1 is that in step 1), the solvent is anhydrous ethanol; the rest is the same as reference example 1. The rest is the same as method example 1.
[0100] like Fig.11 As shown, the lanthanide perovskite oxide La used in the comparative example of the present invention 0.8 Ca 0.2 The peak intensity of CoO3 is weak and there are many impurity peaks, indicating that it is difficult to synthesize lanthanide perovskite oxide materials with complete crystal structure when the solvent is pure ethanol. The reason is that in the sol-gel process, hydrolysis and condensation reactions are key steps. If anhydrous ethanol is used, the hydrolysis reaction will be damaged, making it difficult to form the required three-dimensional network structure. In addition, anhydrous ethanol is volatile, which will cause the reaction rate to be too fast, resulting in incomplete reaction.
[0101] like Fig.12 As shown, the lanthanide perovskite type La used in the comparative example of the present invention 0.8 Ca 0.2 The CoO3 coated material has an irregular block structure with only trace pores and has not formed a favorable conductive network structure. This indicates that in the sol-gel process, the pure anhydrous ethanol system cannot synthesize the required three-dimensional network structure. The reason is that anhydrous ethanol has a low polarity and cannot effectively dissolve metal salts, resulting in poor dispersion of the metal salt mixed solution, which in turn affects the physical properties of the product such as structure and morphology.
[0102] Battery assembly: Same as Example 1.
[0103] like Fig.13 As shown, the lanthanide perovskite type La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has an initial discharge capacity of 202.31 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7 to 4.3 V, and an initial discharge capacity of 198.42 mAh / g at a current density of 1C (200 mA / g, starting from the 4th cycle). After 100 cycles, the discharge capacity is only 153 mAh / g, and the capacity retention rate is only 77.11%, indicating that the synthesized crystalline structure is incomplete, and the irregular morphology of the lanthanide perovskite oxide coated on the surface of the high nickel ternary material will inhibit the capacity. At the same time, the perovskite La synthesized by the mixed solvent in the embodiment of the present invention is 0.8Ca 0.2 Compared with the CoO3 coating effect, the stability is poor.
[0104] Comparative Example 3 The difference between this comparative example and method example 1 is that the lanthanide perovskite oxide La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The preparation method of O2 is wet coating, and the specific preparation method is as follows: 1) Add 0.0485 g (0.112 mmol) of lanthanum nitrate hexahydrate, 0.0066 g (0.028 mmol) of calcium nitrate tetrahydrate and 0.0407 g (0.14 mmol) of cobalt nitrate hexahydrate into 15 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1), and disperse them ultrasonically at an ultrasonic frequency of 50 kHz for 2 h to obtain a metal ion mixed solution; add 0.0294 g (0.14 mmol) of citric acid monohydrate into 5 mL of solvent (the volume ratio of anhydrous ethanol to deionized water is 1:1), and disperse them ultrasonically at an ultrasonic frequency of 50 kHz for 2 h to obtain a 0.028 mol / L citric acid solution; 2) 5 mL of 0.028 mol / L citric acid solution obtained in step 1) was added dropwise at a rate of 90 mL / h to 15 mL of the metal ion mixed solution obtained in step 1) stirred at a stirring speed of 300 r / min, and stirred for 12 h at a water bath temperature of 25 °C and a stirring speed of 300 r / min. Then, 2 g of Ni prepared in Reference Example 5 was added. 0.96 Co 0.03 Mn 0.01 The (OH)2 precursor was heated to 50 °C and stirred for 10 h at 50 °C and 300 r / min. After forming a gel, it was vacuum dried at 100 °C and -0.07 MPa for 10 h to obtain Ni 0.96 Co 0.03 Mn 0.01 (OH)2 precursor coated powder; 3) 1 g (0.0106 mol) of Ni obtained in step 2) 0.96 Co 0.03 Mn 0.01The (OH)2 precursor coated powder and 0.455 g (0.0108 mol) of lithium hydroxide monohydrate were added to an agate mortar and ground at a speed of 150 r / min for 0.5 h until mixed. Then, two-stage temperature rising sintering was carried out in a high-purity oxygen atmosphere. The temperature was first raised to 450 °C at a rate of 5 °C / min, sintered for 4 h, and then raised to 675 °C at a rate of 5 °C / min, sintered for 12 h, and cooled to room temperature to obtain lanthanide perovskite La with an average particle size of 4 μm. 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 O2 positive electrode material.
[0105] Battery assembly: Same as Example 1.
[0106] like Fig.14 As shown, the comparative example of the lanthanide perovskite La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The battery assembled with O2 positive electrode material has an initial discharge capacity of 235.95 mAh / g at a current density of 0.1 C (20 mA / g, first 3 cycles) in the voltage range of 2.7 to 4.3 V. At a current density of 1 C (200 mA / g, starting from the 4th cycle), the initial discharge capacity is 221.28 mAh / g. After 100 cycles, the discharge capacity is only 165.12 mAh / g, and the capacity retention rate is only 74.62%, indicating that although the lanthanide perovskite La 0.8 Ca 0.2 CoO3 coated LiNi 0.96 Co 0.03 Mn 0.01 The initial capacity of the O2 positive electrode material is higher, but the cycle stability is poorer than that of the material obtained by the solid phase coating method in the embodiment of the present invention. The reason is that although the liquid phase coating process does not ball mill the high nickel ternary positive electrode material, which can reduce the damage to the secondary particles and make its initial capacity higher, the Ni 0.96 Co 0.03 Mn 0.01 After the (OH)2 precursor is coated by the liquid phase, high-speed ball milling cannot be performed due to the secondary particles. That is, the perovskite-type oxide material coating layer cannot be ball-milled at 600 r / min after the gel is formed as in step 2 of reference example 1. The particles may be large and unevenly distributed, which will result in a larger volume of the final perovskite material, thereby weakening its performance and ultimately leading to poor cycle stability after coating.
Claims
1. A lanthanide perovskite oxide-coated high-nickel ternary positive electrode material, characterized in that: The lanthanide perovskite oxide coated high nickel ternary positive electrode material is a spherical particle formed by coating a high nickel ternary positive electrode material with a lanthanide perovskite oxide coating layer at a mass ratio of 0.01 to 0.03:1; the chemical formula of the lanthanide perovskite oxide is La z Ca 1- z CoO3, wherein 0.5≤z≤1.0; the chemical formula of the high nickel ternary positive electrode material is LiNi x Co y Mn (1-x-y) O2, where 0.80≤x≤0.96, 0.01≤y≤0.10, 1-xy>0.
2. The lanthanide perovskite oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: The high-nickel ternary positive electrode material is a typical layered structure, and the three elements Ni, Co, and Mn are evenly distributed in the high-nickel ternary positive electrode material; the average particle size of the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material is 2 to 8 μm; the average thickness of the lanthanide perovskite oxide coating layer is 2 to 6 nm.
3. A method for preparing the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material as claimed in claim 1 or 2, characterized in that: The lanthanide perovskite oxide is mixed with the high-nickel ternary positive electrode material by ball milling, and then sintered at low temperature under a protective atmosphere.
4. The method for preparing the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material according to claim 3, characterized in that: The mass ratio of the lanthanide perovskite oxide to the high-nickel ternary positive electrode material is 0.01-0.03:1; the rotation speed of the ball milling mixing is 100-300 r / min, and the time is 2-10 h; the protective atmosphere includes argon and / or nitrogen; the low-temperature sintering is to increase the temperature to 300-550°C at a rate of 1-10°C / min and sinter for 2-10 h.
5. The method for preparing the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material according to claim 3 or 4, characterized in that: The method for preparing the lanthanide perovskite-type oxide comprises the following steps: 1) adding a lanthanum source, a calcium source and a cobalt source into a solvent, and dispersing them by ultrasonic method to obtain a metal ion mixed solution; adding a complexing agent into a solvent, and dispersing them by ultrasonic method to obtain a complexing agent solution; 2) adding the complexing agent solution obtained in step 1) drop by drop into the metal ion mixed solution obtained in step 1), or adding the metal ion mixed solution obtained in step 1) drop by drop into the complexing agent solution obtained in step 1), performing a stirring reaction, heating, performing a second stirring reaction, drying, ball milling, sintering in an oxidizing atmosphere, and cooling to room temperature to obtain a lanthanide perovskite oxide.
6. The method for preparing the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material according to claim 5, characterized in that: In step 1), the molar ratio of lanthanum element in the lanthanum source, calcium element in the calcium source and cobalt element in the cobalt source is 0.5-1.0:0-0.5:1; the total molar concentration of metal ions in the metal ion mixed solution is 0.1-0.9 mol / L; the lanthanum source includes lanthanum nitrate, lanthanum acetate or lanthanum chloride, and one or more of their hydrates; the calcium source includes calcium nitrate, calcium acetate or calcium chloride, and one or more of their hydrates; the cobalt source includes cobalt nitrate, cobalt acetate or cobalt chloride, and one or more of their hydrates; the concentration of the complexing agent solution is 0.1-0.8 mol / L; the complexing agent includes one or more of citric acid, ethylenediaminetetraacetic acid or ethylene glycol; the solvents are all mixed solvents of anhydrous ethanol and deionized water in a volume ratio of 1:1-3; the frequency of the ultrasonic dispersion is 30-60 kHz, and the time is 1-4 h.
7. The method for preparing the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material according to claim 5 or 6, characterized in that: In step 2), the volume ratio of the complexing agent solution to the metal ion mixed solution is 1:0.4-4.0; the molar ratio of the complexing agent in the complexing agent solution to the cobalt ion in the metal ion mixed solution is 1.0-1.5:1; the rate of the dropwise addition is 60-120 mL / h; during the dropwise addition, the metal ion mixed solution or the complexing agent solution is stirred at a stirring speed of 100-600 r / min; the temperature of the first stirring reaction is 20-30 ° C, the stirring speed is 100-600 r / min, and the time is 10-20 h; the temperature is raised to 30-80 ° C; the temperature of the second stirring reaction is 30-80 ° C, the stirring speed is 100-600 r / min, and the time is 8-14 h; the drying is vacuum drying; the temperature of the vacuum drying is 80-120 ° C, the vacuum degree is -0.06--0.09 MPa, and the time is 6-12 h; the rotation speed of the ball mill is 300-700 r / min, and the time is 2-10 h; the oxidizing atmosphere includes an oxygen atmosphere and / or an air atmosphere; the sintering is a two-stage temperature-raising sintering, firstly heating to 350-550°C at a rate of 1-10°C / min, sintering for 2-10 h, and then heating to 600-900°C at a rate of 1-10°C / min, and sintering for 9-16 h.
8. The method for preparing the lanthanide perovskite oxide-coated high-nickel ternary positive electrode material according to any one of claims 3 to 7, characterized in that: The preparation method of the high-nickel ternary positive electrode material is as follows: grind and mix the nickel cobalt manganese hydroxide precursor and the lithium source, sinter them in an oxidizing atmosphere, and cool them to room temperature; the chemical formula of the nickel cobalt manganese hydroxide precursor is Ni x Co y Mn (1-x-y) (OH)2, wherein 0.80≤x≤0.96, 0.01≤y≤0.10, 1-xy>0; the average particle size of the nickel cobalt manganese hydroxide precursor is 2-8 μm; the molar ratio of the total molar number of Ni, Co, and Mn in the nickel cobalt manganese hydroxide precursor to the molar ratio of Li in the lithium source is 1:1.01-1.08; the lithium source includes LiOH·H2O and / or Li2CO3; the grinding speed is 100-300 r / min, and the time is 12-48 min; the oxidizing atmosphere includes oxygen atmosphere and / or air atmosphere; the sintering is a two-stage temperature rising sintering, firstly heating to 350-550°C at a rate of 1-10°C / min, sintering for 2-6 h, and then heating to 550-800°C at a rate of 1-10°C / min, and sintering for 8-14 h.
Citation Information
Patent Citations
La1-xCaxCoO3 coated lithium ion battery cathode material LiNi1 / 3Co1 / 3Mn1 / 3O2 and preparation method thereof
CN103413924A
Perovskite type conductor material coated ternary positive electrode material, preparation method thereof and lithium ion battery
CN111933910A
Ternary positive electrode material coated with perovskite type conductor and preparation method of ternary positive electrode material
CN116979039A
High-nickel ternary positive electrode composite material as well as preparation method and application thereof
CN118899420A
Positive electrode active material for use in lithium ion secondary cell
US20170155134A1
Cited By
Modified positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN121460538A
High-nickel layered positive electrode material containing embedded perovskite-spinel double skeleton, and preparation method and application thereof
CN122916235A